Penerapan Perilaku Hidup Bersih Dan Sehat Rumah Tangga di Wilayah Kerja Puskesmas Pattalassang Desa Borongpa’la’la Kabupaten Gowa - Ilyas, Muhammad; Syafar, Muhammad; Azis, Rahmawati; Nurambiya, Nurambiya (Asosiasi Guru dan Dosen Seluruh Indonesia, 2024)
This research aims to analyze the implementation of Clean and Healthy Living Behavior (PHBS) in households in the work area of ​​the Patalassang Community Health Center, Gowa Regency. This research aims to examine the encouraging and inhibiting factors for household PHBS implementation.Qualitative research methods using sentiment analysis research methods and assisted by data analysis software called MAXQDA were used to explore the driving and inhibiting factors in implementing PHBS through in-depth interviews, focus group discussions and observations. The research results show that adequate knowledge about PHBS, social support, both from family, community health centers and the government, as well as educational programs run by community health centers are the main driving factors. On the other hand, lack of knowledge, low personal awareness, and limited facilities such as sanitation, clean water and proper toilets are significant obstacles in implementing PHBS. The conclusions of this research emphasize the importance of increasing health education, strengthening social support, providing adequate sanitation facilities, and increasing individual awareness and motivation to achieve optimal PHBS implementation. With an integrated and collaborative approach, it is hoped that the implementation of PHBS in households in the Patalassang Community Health Center working area can continue to be improved, thus contributing to improving the overall quality of community health.